Design and development of a multi-channel receiver - Zeng, Yu (2009)
In the wireless communication system, the smart antenna system was explored and developed to trace the accurate signal. In this project, a 4-channel GSM receiver was designed and built to be used as part of digital communication system. After received by the antenna, the Signals are to be down-converted from 960 MHz to 80 MHz in the first processing stage. In the second stage, the signal will down to 2 MHz where they will be converted to digital form for the further processing. Design and verification is one of the most important and interesting part. In order to build an ideal system, hundreds of literature reviews have been done before the implementation. After the design finished, the simulation were conducted to prove our assumption. In this project, testing is conducted during the whole project plan not only in the design consideration but also in the final implementation. The whole receiver system was constructed under testing and data analysis. In the end, the fabrication and integration of four-channel receiver system were accomplished as an end of this project.